2007
DOI: 10.1111/j.1532-5415.2007.01429.x
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness in Older Chinese Adults: A Risk Factor for Elder Mistreatment

Abstract: Loneliness appeared to be a risk factor associated with elder mistreatment in this older Chinese population. Further prospective studies are needed to confirm this finding. An exploration of Chinese culture and tradition may yield insight into shaping a prevention framework for mistreatment of older Chinese people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 23 publications
2
74
0
1
Order By: Relevance
“…Financial dependence on children, sex, and education were found to be associated with any mistreatment, while financial dependence was also a significant predictor of elder abuse. The results of our study are consistent with findings elsewhere that sex, lower education, and income dependency were demographic risk factors associated with elder abuse and neglect (Dong, Simon, & Gorbien, 2007). The overall prevalence of elder abuse as reported in this study is over 4% higher than that reported in an earlier study done in Iran (Karimi & Elahi, 2008), but it is comparable with the results of Chokkanathan and Lee (2006) who reported a 14% prevalence rate of elder mistreatment in Chennai, India.…”
Section: Discussionsupporting
confidence: 92%
“…Financial dependence on children, sex, and education were found to be associated with any mistreatment, while financial dependence was also a significant predictor of elder abuse. The results of our study are consistent with findings elsewhere that sex, lower education, and income dependency were demographic risk factors associated with elder abuse and neglect (Dong, Simon, & Gorbien, 2007). The overall prevalence of elder abuse as reported in this study is over 4% higher than that reported in an earlier study done in Iran (Karimi & Elahi, 2008), but it is comparable with the results of Chokkanathan and Lee (2006) who reported a 14% prevalence rate of elder mistreatment in Chennai, India.…”
Section: Discussionsupporting
confidence: 92%
“…Based on a well-characterized community-based cohort, clinical depression was significantly associated with elder abuse cases reported to APS [8]. In another clinical-based cohort studied by Dong et al [9], loneliness was also associated with an increased risk of elder abuse. …”
Section: Resultsmentioning
confidence: 99%
“…After EBC collection, FENO levels were recorded with a chemiluminescence analyzer (Model LR2000, Logan Research, Rochester, UK) without wearing a nose clip by slow exhalation (5–6 liters/min) from total lung capacity for 20–30 s against a resistance (5 cm H 2 O) to prevent nasal contamination [15]. Three successive recordings were made and the mean of these values was used in all calculations.…”
Section: Methodsmentioning
confidence: 99%